Solvation Structure Determination Of Ni2+ Ion In Water By Means Of Monte Carlo Method = Penentuan Struktur Solvasi Ion Ni2+ di dalam Air dengan Metode Monte Carlo - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT Determination of solvation structure of Ni2+ ion in water has been achieved using Monte Carlo method using canonic assemble (NVT constant). Simulation of a Ni2+ ion in 215 H2O molecules has been done under NVT condition (298.15 K). The results showed that number of H2O molecules surround Ni2+ ion were 8 molecules in first shell and 17 molecules in second shell, interaction energy of Ni2+-H20 in first shell was -68.7 kcal/mol and in second shell was -9.8 kcal/mol, and there were two angles of 0-Ni2+-0, i.e. 74Â° and 142Â°. According to those results, the solvation structure of Ni2+ ion in water was cubic antisymetric.